Architekturzeichnungen der deutschen Renaissance: Funktion und Bildlichkeit zeichnerischer Produktion 1500-1650 - Fitzner, Sebastian (Modern Academic Publishing, 2016)
ation such as the registry, the library, and the armoury, but also in the Cabinet of Curiosities, or in the architect's personal archive. Even with only a small number of known approaches theorizing architectural drawings and design practices during the 16th century, it is possible to reveal a broad influence on drawing theories, especially by perspective treatises and the so-called »Visier- und Messkunst« (measuring). Reconstructing the various places of producing, collecting, displaying, and studying architectural drawings shows that architectural drawings were a crucial part in cultural processes of understanding, organizing, and dealing with the built environment.